Резание материалов и режущий инструмент учебное пособие - Кирсанов, С. В. специалист в области машиностроения профессор Томского политехнического университета, доктор технических наук 1949- (Изд-во ТПУ, 2014)
The subject of this book is the machining processes. The general information about the cutting of materials, chip formation, complex cutting patterns, heat, strength, wear resistance, tool life, machinability of materials and features of the process of cutting with multiple point cutting tools and grinding tools is given in the first part. Questions of calculation and optimization of design and geometrical parameters of the common types of cutting tools, with respect to the cutting conditions, properties of cutting tool and workpiece materials, as well as the requirements for dimensional accuracy and surface finish, are examined in the second part of the book. The book is recommended for English-speaking students following the Bachelor Degree Program in Mechanical Engineering at Tomsk Polytechnic University.